Religious Engagement and Students’ Academic Achievement - Malani Mahrezeki (Young Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the influence of religious involvement on student academic achievement at MTsN Simpang Tiga, Bener Meriah Regency. Using a quantitative approach and involving 30 respondents, this study measured the extent to which students' participation in religious activities outside of class contributed to their academic achievement. Data were analyzed using SPSS software through linear regression tests, coefficient of determination tests, and model significance tests. The results indicate a strong relationship between religious involvement and student achievement. This finding strengthens the argument that religious activities have pedagogical, psychological, and social functions that play a role in building discipline, intrinsic motivation, and a more stable learning orientation.